Active ester type curing agent, curable resin composition, curable film, and laminated film
The curable resin composition with a rubber component, epoxy group compound, active ester curing agent, and filler addresses the high flowability and dielectric property challenges of styrene elastomers, providing a cured product with improved adhesion and low dielectric properties for printed wiring boards.
Patent Information
- Application Number
- JP2024108253
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-06
- Filing Date
- 2024-07-04
- Publication Date
- 2025-01-20
AI Technical Summary
Adhesive compositions using styrene elastomers yield cured products with excellent dielectric properties but have high flowability, which can lead to insufficient embedding of printed wiring board circuits.
A curable resin composition containing a rubber component, a compound with an epoxy group, an active ester curing agent, a curing accelerator, and a filler, with specific ratios and components to achieve high flowability and low dielectric properties in a high frequency region.
The composition forms a cured product with high flowability and excellent low dielectric properties, suitable for interlayer adhesives in multilayer printed wiring boards, enhancing adhesion and reducing dielectric loss.
Smart Images

Figure 2025010113000001 
Figure 2025010113000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an active ester-type curing agent, a curable resin composition, a curable film, and a laminate film. [Background technology]
[0002] In recent years, as the transmission speed of signals in printed wiring boards increases, the frequency of the signals is also increasing. Accordingly, there is an increasing demand for printed wiring boards to have low dielectric properties (low dielectric constant, low dielectric loss tangent) in the high frequency range. In addition, protective layers (coverlays) that cover the circuits of printed wiring boards, interlayer adhesives in multilayer printed wiring boards, and the like are also required to have low dielectric properties in addition to adhesion to substrates, etc. As a resin composition that can give a cured product with low dielectric properties, for example, Patent Document 1 proposes an adhesive composition containing a styrene-based elastomer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-150543 A Summary of the Invention [Problem to be solved by the invention]
[0004] Adhesive compositions using the above-mentioned elastomers tend to easily give cured products with excellent dielectric properties. However, when used as interlayer adhesives or the like, high flow properties may be required in order to sufficiently embed the circuits of printed wiring boards.
[0005] The present disclosure has been made in consideration of the above circumstances, and has an object to provide an active ester type curing agent, a curable resin composition, a curable film, and a laminate film that are capable of forming a cured product having high flowability and excellent low dielectric properties in the high frequency range. [Means for solving the problem]
[0006] In order to solve the above problems, the present disclosure provides the following curable resin composition, curable film, laminated film, and active ester-type curing agent.
[0007] [1] A curable resin composition comprising: (A) a rubber component; (B) a compound having an epoxy group; (C) an active ester type curing agent; (D) a curing accelerator; and (E) a filler, wherein the (C) active ester type curing agent contains an active ester of an alkylphenol resin. [2] The curable resin composition according to the above [1], which is used as an interlayer adhesive for a multilayer printed wiring board. [3] The curable resin composition according to the above [1] or [2], wherein the content of the (C) active ester type curing agent is 1 to 40 parts by mass per 100 parts by mass of the total amount of the (A) rubber component, the (B) compound having an epoxy group, and the (C) active ester type curing agent. [4] The curable resin composition according to any one of the above [1] to [3], wherein the compound having an epoxy group (B) has a weight average molecular weight of 200 to 1,000. [5] The curable resin composition according to any one of the above [1] to [4], wherein the content of the (D) curing accelerator is 0.1 to 10 parts by mass per 100 parts by mass of the total amount of the (A) rubber component, the (B) the compound having an epoxy group, and the (C) the active ester type curing agent. [6] The curable resin composition according to any one of the above [1] to [5], wherein the (E) filler includes a surface-treated filler. [7] The curable resin composition according to [6] above, wherein the surface-treated filler comprises a filler having at least one group selected from the group consisting of an epoxy group, a vinyl group, and a phenylamino group. [8] A curable film comprising the curable resin composition according to any one of the above [1] to [7]. [9] A laminate film comprising a base film and the curable film according to [8] above provided on the base film.
[10] An active ester type curing agent, including an active ester of an alkylphenol resin. Effect of the Invention
[0008] According to the present disclosure, it is possible to provide an active ester type curing agent, a curable resin composition, a curable film, and a laminate film that can form a cured product having high flowability and excellent low dielectric properties in the high frequency range. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, several embodiments of the present disclosure will be described in detail. However, the present disclosure is not limited to the following embodiments.
[0010] In this specification, the numerical range indicated by "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range may be replaced with the upper limit or lower limit of the numerical range of another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. When referring to the amount of each component in the composition in this specification, if there are multiple substances corresponding to each component in the composition, it means the total amount of the multiple substances present in the composition unless otherwise specified. "A or B" may contain either A or B, or may contain both. "Solid content" refers to the non-volatile content in the resin composition excluding volatile substances (water, solvent, etc.). In other words, "solid content" refers to components other than the solvent that remain without volatilization during drying of the resin composition described later, and also includes components that are liquid, syrup-like, or waxy at room temperature (25°C). In this specification, for example, "(meth)acrylic acid" means "acrylic acid" and the corresponding "methacrylic acid", and the same applies to other similar words.
[0011] [Curable resin composition] The curable resin composition according to the present embodiment contains (A) a rubber component, (B) a compound having an epoxy group, (C) an active ester type curing agent, (D) a curing accelerator, and (E) a filler, and the (C) active ester type curing agent contains an active ester of an alkylphenol resin.
[0012] The curable resin composition according to the present embodiment can be used for forming a protective layer (coverlay) for covering an electric circuit in a printed wiring board, and as an interlayer adhesive in a multilayer printed wiring board. The curable resin composition according to the present embodiment has adhesion to an adherend, for example, a material constituting a printed wiring board such as a metal part or a substrate of a printed wiring board, and when used as an interlayer adhesive, it can form a cured product having sufficiently high flowability and excellent low dielectric properties in a high frequency range. Hereinafter, each component that can be contained in the curable resin composition will be described.
[0013] <(A) Rubber component> The (A) rubber component can include, for example, at least one type of rubber selected from the group consisting of acrylic rubber, isoprene rubber, butyl rubber, styrene butadiene rubber, butadiene rubber, styrene butylene styrene rubber, styrene ethylene propylene styrene rubber, styrene ethylene butylene styrene rubber, acrylonitrile butadiene rubber, silicone rubber, urethane rubber, chloroprene rubber, ethylene propylene rubber, fluororubber, vulcanized rubber, epichlorohydrin rubber, and chlorinated butyl rubber.
[0014] From the viewpoint of reducing the influence of moisture absorption on insulation reliability, reducing the influence on connection reliability, and reducing damage to wiring, a rubber component with low gas permeability may be used. From such a viewpoint, the (A) rubber component may contain at least one selected from styrene-butadiene rubber, butadiene rubber, styrene-ethylene-butylene-styrene rubber, and butyl rubber. The (A) rubber component may contain styrene-ethylene-butylene-styrene rubber.
[0015] Examples of commercially available acrylic rubbers include the "Nipol AR Series" from Zeon Corporation and the "Clarity Series" from Kuraray Co., Ltd. Examples of commercially available isoprene rubbers include the "Nipol IR Series" from Zeon Corporation. Examples of commercially available butadiene rubbers include the "Nipol BR Series" from Zeon Corporation. Examples of commercially available acrylonitrile butadiene rubbers include the "NBR Series" from ENEOS Material Co., Ltd. Examples of commercially available silicone rubbers include the "KMP Series" from Shin-Etsu Silicone Co., Ltd. Examples of commercially available ethylene propylene rubbers include the "EP Series" from ENEOS Material Co., Ltd. Examples of commercially available fluororubbers include the "Dai-El Series" from Daikin Co., Ltd. Examples of commercially available epichlorohydrin rubbers include the "Hydrin Series" from Zeon Corporation.
[0016] The rubber component (A) can also be prepared by synthesis. For example, acrylic rubber can be obtained by reacting (meth)acrylic acid, (meth)acrylic acid esters, aromatic vinyl compounds, vinyl cyanide compounds, etc.
[0017] The rubber component (A) may contain a rubber having a crosslinking group. The use of a rubber having a crosslinking group tends to improve the strength, heat resistance, and adhesion of the cured product. The crosslinking group may be any reactive group capable of proceeding with a reaction that crosslinks the molecular chains of the rubber component (A). Examples of the crosslinking group include reactive groups, acid anhydride groups, amino groups, hydroxyl groups, epoxy groups, and carboxy groups of compounds having an epoxy group (B) described later.
[0018] The (A) rubber component may contain a rubber having at least one crosslinking group of an acid anhydride group or a carboxyl group. An example of a rubber having an acid anhydride group is a rubber partially modified with maleic anhydride. The rubber partially modified with maleic anhydride is a polymer containing a structural unit derived from maleic anhydride. The (A) rubber component may contain a rubber partially modified with maleic anhydride. An example of a commercially available product of a rubber partially modified with maleic anhydride is a styrene-based elastomer "Tufprene 912" manufactured by Asahi Kasei Corporation.
[0019] The rubber partially modified with maleic anhydride may be a hydrogenated styrene-based elastomer partially modified with maleic anhydride. The hydrogenated styrene-based elastomer is expected to have the effects of improving connection reliability, insulation reliability, and weather resistance. The hydrogenated styrene-based elastomer is an elastomer obtained by adding hydrogen to the unsaturated double bonds of a styrene-based elastomer having a soft segment containing an unsaturated double bond. Examples of commercially available hydrogenated styrene-based elastomers partially modified with maleic anhydride include "FG1901" and "FG1924" from Kraton Polymer Japan Co., Ltd., and "Tuftec M1911", "Tuftec M1913", and "Tuftec M1943" from Asahi Kasei Corporation. The hydrogenated styrene-based elastomer partially modified with maleic anhydride may be a hydrogenated styrene ethylene butylene styrene elastomer partially modified with maleic anhydride.
[0020] The weight average molecular weight (Mw) of the (A) rubber component may be, from the viewpoints of coating property and circuit embedding property, 20,000 to 200,000, 30,000 to 150,000, 50,000 to 150,000, 80,000 to 140,000, or 100,000 to 140,000. Mw means a value calculated in terms of standard polystyrene determined by gel permeation chromatography (GPC).
[0021] In the curable resin composition, the content of the rubber component (A) is preferably 50 to 90 mass%, more preferably 55 to 80 mass%, and even more preferably 60 to 70 mass%, based on the total amount of the rubber component (A), the compound having an epoxy group (B), and the ester-based curing agent (C). When the content of the rubber component (A) is 60 mass% or more, the rubber component and the compound having an epoxy group tend to mix well. When the content of the rubber component (A) is 95 mass% or less, the obtained cured product tends to have particularly excellent properties in terms of adhesion, connection reliability, insulation reliability, and heat resistance. The content of the rubber component (A) in the cured product may be within the above range based on the mass of the cured product.
[0022] <(B) Compound Having an Epoxy Group> The compound having an epoxy group (B) is not particularly limited as long as it has an epoxy group in the molecule, and can be, for example, a general epoxy resin. The epoxy resin may be monofunctional, bifunctional, or polyfunctional (three or more functional), and is not particularly limited, but from the viewpoint of obtaining more sufficient curability, a bifunctional or polyfunctional epoxy resin may be used.
[0023] Examples of the epoxy resin include bisphenol A type, bisphenol F type, phenol novolac type, naphthalene type, dicyclopentadiene type, and cresol novolac type epoxy resins. From the viewpoint of low tackiness, dielectric properties, and heat resistance, a naphthalene type or dicyclopentadiene type epoxy resin may be selected as the compound having an epoxy group (B), or a dicyclopentadiene type epoxy resin may be selected. These epoxy resins may be used alone or in combination of two or more.
[0024] The combination of a rubber having a maleic anhydride group or a carboxyl group with a compound having an epoxy group (epoxy resin) tends to provide particularly excellent effects in terms of heat resistance, low moisture permeability, and adhesiveness of the cured product. Improved heat resistance of the cured product can suppress deterioration of the cured product during heating processes such as nitrogen reflow.
[0025] The weight average molecular weight (Mw) of the compound having an epoxy group (B) may be, for example, 200 to 2000. From the viewpoints of the fluidity of the resin composition and the dielectric properties of the cured product, the weight average molecular weight (Mw) is preferably 200 to 1000, more preferably 250 to 800, even more preferably 300 to 550, and particularly preferably 350 to 450.
[0026] The number average molecular weight (Mn) of the compound having an epoxy group (B) may be, for example, 100 to 1,000. From the viewpoints of the fluidity of the resin composition and the dielectric properties of the cured product, it is preferably 150 to 500, more preferably 200 to 400, even more preferably 250 to 350, and particularly preferably 250 to 300.
[0027] The above-mentioned Mw and Mn refer to values calculated in terms of standard polystyrene determined by gel permeation chromatography (GPC).
[0028] The epoxy equivalent of the compound having an epoxy group (B) may be, for example, 200 to 330 g / eq. However, from the viewpoints of the fluidity of the resin composition and the dielectric properties of the cured product, it may be 220 to 310 g / eq, 220 to 290 g / eq, 220 to 270 g / eq, or 230 to 260 g / eq.
[0029] The curable resin composition may contain a component having a polymerizable functional group other than the compound having an epoxy group (B) within a range that does not significantly impair the effects of the present disclosure. From the viewpoint of further reducing the dielectric tangent of the cured product, the content of the component having a polymerizable functional group is preferably less than 10 parts by mass relative to 100 parts by mass of the compound having an epoxy group (B).
[0030] <(C) Active ester type hardener> The (C) active ester type curing agent is a compound which itself participates in the curing reaction. When the (C) active ester type curing agent contains the (C1) active ester of an alkylphenol resin, it is possible to achieve both flowability of the curable resin composition and dielectric properties of the cured product.
[0031] The active ester (C1) is a reaction product of an alkylphenol resin, an aromatic dicarboxylic acid halide, and a monohydroxy compound, and has an active ester group formed by esterifying a hydroxyl group of the alkylphenol resin. The active ester (C1) may contain residual phenolic hydroxyl groups.
[0032] The alkylphenol resin has an alkyl group and a phenolic hydroxyl group. The alkylphenol resin may be a polymer having a skeleton derived from an alkylphenol compound. The alkylphenol resin may further have a formaldehyde skeleton. As the alkylphenol resin, for example, products under the trade names "PR1501" and "PR1140" manufactured by Resonac Co., Ltd. are available.
[0033] Examples of aromatic dicarboxylic acid halides include acid chlorides, acid fluorides, acid bromides, and acid iodides of aromatic dicarboxylic acids such as isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid. Examples of aromatic dicarboxylic acid halides include aromatic dicarboxylic acid chlorides. Examples of monohydroxy compounds include naphthol compounds such as α-naphthol and β-naphthol; and phenol compounds such as phenol, o-cresol, m-cresol, p-cresol, and 3,5-xylenol.
[0034] The (C) active ester type curing agent may further contain an active ester type curing agent (C2) other than the active ester compound (C1).
[0035] The active ester type curing agent (C2) is not particularly limited, but from the viewpoint of obtaining a better effect of improving heat resistance and reducing dielectric tangent, an active ester having a dicyclopentadiene skeleton, an active ester having a naphthalene skeleton, etc. are preferably used. Examples of commercially available products of the active ester type curing agent (C2) include "EPICLON HPC8000-65T", "EPICLON HPC8000-L-65MT", "EPICLON HPC8150-60T", "EPICLON HPC8150-62T", and "EPICLON HPC8150-65T" (all of which are trade names manufactured by DIC Corporation), etc.
[0036] In the curable resin composition, the content of the (C) active ester type curing agent may be 1 part by mass or more, 3 parts by mass or more, 5 parts by mass or more, or 8 parts by mass or more, and 40 parts by mass or less, 35 parts by mass or less, 30 parts by mass or less, or 25 parts by mass or less, relative to 100 parts by mass of the total amount of the (A) rubber component, the (B) compound having an epoxy group, and the (C) active ester type curing agent. That is, the content of the (C) active ester type curing agent may be 1 to 40 parts by mass, 3 to 35 parts by mass, 5 to 30 parts by mass, or 8 to 25 parts by mass, relative to 100 parts by mass of the total amount of the (A) rubber component, the (B) compound having an epoxy group, and the (C) active ester type curing agent. When the total content of the (B) compound having an epoxy group and the (C) active ester type curing agent is 1 part by mass or more, the flowability of the curable resin composition is easily increased, and the cured product tends to have particularly excellent properties in terms of adhesion, insulation reliability, and heat resistance. When the total content of the (B) compound having an epoxy group and the (C) active ester type curing agent is 40 parts by mass or less, more sufficient low dielectric properties, adhesion, and elasticity are easily obtained, and the composition tends to mix well with the rubber component.
[0037] In the curable resin composition, the content ratio of the compound having an epoxy group (B) to the active ester type curing agent (C), in terms of the equivalent ratio of the epoxy group in the compound having an epoxy group (B) to the ester bond in the active ester type curing agent (C), is preferably in the range of 4:5 to 5:4. By having the content ratio within the above range, more sufficient curing is easily obtained, and the cured product tends to have particularly excellent properties in terms of dielectric properties, adhesiveness, insulation reliability, and heat resistance.
[0038] <(D) Curing accelerator> The (D) curing accelerator is a compound that functions as a catalyst for the curing reaction. The (D) curing accelerator may be selected from tertiary amines, imidazoles, organic acid metal salts, phosphorus compounds, Lewis acids, amine complex salts, and phosphines. Among these, imidazole may be used from the viewpoints of storage stability of the varnish of the curable resin composition, curability, and dielectric properties of the cured product. When the (A) rubber component contains a rubber partially modified with maleic anhydride, an imidazole compatible with the rubber may be selected. The imidazole may be 1-benzyl-2-methylimidazole.
[0039] In the curable resin composition, the content of the (D) curing accelerator may be 0.1 to 10 parts by mass relative to 100 parts by mass of the total amount of the (A) rubber component, the (B) compound having an epoxy group, and the (C) active ester type curing agent. When the content of the (D) curing accelerator is 0.1 parts by mass or more, more sufficient curing tends to be easily obtained. When the content of the (D) curing accelerator is 10 parts by mass or less, the storage stability of the varnish, film, etc. of the curable resin composition, the heat resistance of the cured product, and the dielectric properties tend to be improved. From the above viewpoints, the content of the (D) curing accelerator may be 0.1 to 7 parts by mass, 0.2 to 5 parts by mass, or 0.3 to 3 parts by mass.
[0040] <(E) Filler> When the curable resin composition contains a filler (E), the coefficient of linear expansion (CTE) of the cured product tends to be reduced.
[0041] The (E) filler may be a filler having at least one group selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group, and a phenylamino group. By having these groups, the filler tends to have particularly excellent properties in terms of compatibility with the resin component at the filler interface, dispersibility of the filler, storage stability of the curable resin composition, linear expansion coefficient of the cured product, and adhesiveness of the cured product. Therefore, the curable resin composition can be more suitably used as an interlayer adhesive for multilayer printed wiring boards.
[0042] From the viewpoints of linear expansion coefficient and adhesiveness, the (E) filler preferably contains a filler having at least one group selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group, and a phenylamino group, more preferably contains a filler having at least one group selected from the group consisting of a vinyl group, an epoxy group, and a phenylamino group, and even more preferably contains a filler having an epoxy group.
[0043] As the (E) filler, from the viewpoints of the linear expansion coefficient and adhesion to a resin substrate having low polarity, a filler having a vinyl group or an epoxy group is more preferable, and from the same viewpoint, a filler having an epoxy group is particularly preferable. An example of a resin substrate having low polarity is a liquid crystal polymer.
[0044] The (E) filler may be a filler that has been subjected to a surface treatment. The surface-treated filler can be obtained by treating the surface of the filler with a surface treatment agent such as an organic silane compound. By treating the surface of the filler, the filler tends to have particularly excellent properties in terms of compatibility with the resin component at the filler interface, dispersibility of the filler, storage stability of the curable resin composition, linear expansion coefficient of the cured product, and adhesiveness of the cured product. Therefore, by using a surface-treated filler as the (E) filler, the curable resin composition can be more suitably used as an interlayer adhesive for a multilayer printed wiring board. The surface treatment may be a surface modification.
[0045] From the viewpoints of linear expansion coefficient and adhesiveness, the surface-treated filler preferably contains a filler having at least one group selected from the group consisting of a (meth)acryloyl group, a vinyl group, an epoxy group, and a phenylamino group, more preferably contains a filler having at least one group selected from the group consisting of a vinyl group, an epoxy group, and a phenylamino group, and even more preferably contains a filler having an epoxy group.
[0046] As the surface-treated filler, from the viewpoints of the linear expansion coefficient and adhesion to a resin substrate having low polarity, a filler having a vinyl group or an epoxy group is more preferable, and from the same viewpoint, a filler having an epoxy group is particularly preferable. An example of a resin substrate having low polarity is a liquid crystal polymer.
[0047] When the above-mentioned surface-treated filler is used, the cured product of the curable resin composition tends to have improved adhesion to materials constituting a printed wiring board, and in particular, tends to have improved adhesion to a substrate having a low-roughening or non-roughening surface. The cured product of the curable resin composition containing the above-mentioned surface-treated filler tends to have good adhesion to a low-polarity resin substrate, for example, a non-roughening liquid crystal polymer film.
[0048] From the viewpoint of achieving both the flowability of the curable resin composition and a reduced linear expansion coefficient of the cured product, the content of the (E) filler may be 30 to 75 mass%, 30 to 70 mass%, 40 to 70 mass%, or 50 to 65 mass% based on the total solid content of the curable resin composition. When the content of the (E) filler is within the above range, it is possible to achieve both the flowability of the curable resin composition and a reduced linear expansion coefficient of the cured product.
[0049] From the viewpoint of achieving excellent dielectric properties, adhesiveness, and film appearance of the cured product, the average particle size of the (E) filler may be 0.01 μm or more, 0.1 μm or more, or 0.2 μm or more, and may be 5.0 μm or less, 4.0 μm or less, 3.0 μm or less, 1.0 μm or less, or 0.8 μm or less. The average particle size of the (E) filler means the particle size at a cumulative frequency of 50% in the particle size distribution determined by a laser diffraction / scattering method.
[0050] (E) As the filler, an inorganic filler may be used from the viewpoint of further reducing the linear expansion coefficient and improving the elastic modulus. Examples of the inorganic filler include fillers containing at least one inorganic substance selected from the group consisting of silica, alumina, titania, tantalum oxide, zirconia, silicon nitride, gallium oxide, boron nitride, barium titanate, barium carbonate, magnesium carbonate, aluminum hydroxide, magnesium hydroxide, lead titanate, lead titanate zirconate, lead lanthanum titanate zirconate, spinel, mullite, cordierite, talc, aluminum titanate, yttria-containing zirconia, barium sulfate, barium silicate, calcium carbonate, calcium sulfate, zinc oxide, and magnesium titanate. The inorganic filler may be used alone or in combination of two or more. Among these, the inorganic filler may be an inorganic filler containing any one of silica, alumina, titania, or boron nitride from the viewpoint of dispersibility and heat resistance of the cured product. The inorganic filler may be an inorganic filler containing silica from the viewpoint of dielectric properties.
[0051] As the (E) filler, an organic filler may be used. Examples of the organic filler include fillers made of liquid crystal polymer (LCP) and polytetrafluoroethylene (PTFE). The organic filler may be used alone or in combination of two or more. Furthermore, as the (E) filler, one or more inorganic fillers may be used in combination with one or more organic fillers.
[0052] From the viewpoints of dispersibility and heat resistance, the (E) filler may be an inorganic filler whose surface is treated with silica, alumina, titania, or boron nitride, or from the viewpoints of linear expansion coefficient and adhesiveness, the (E) filler may be a surface-treated silica filler whose surface is treated with silica.
[0053] As a surface treatment agent for inorganic fillers, from the viewpoints of linear expansion coefficient and adhesiveness, organic silane compounds such as epoxy silane compounds, amino silane compounds, (meth)acrylic silane compounds, and vinyl silane compounds may be used.
[0054] Examples of the organic silane compound include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-phenylaminopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, and a and 3-(1,3-dimethylbutylidene)-3-aminopropyltriethoxysilane.
[0055] <Other ingredients> In addition to the above-mentioned components, the curable resin composition may further contain, as necessary, an antioxidant, an anti-yellowing agent, an ultraviolet absorber, a visible light absorber, a colorant, a plasticizer, a stabilizer, a filler, a flame retardant, a leveling agent, and the like, as long as the effects of the present disclosure are not significantly impaired.
[0056] In particular, the curable resin composition may contain at least one deterioration inhibitor selected from the group consisting of antioxidants, heat stabilizers, light stabilizers, and hydrolysis inhibitors. The antioxidant suppresses deterioration due to oxidation. In addition, the antioxidant imparts sufficient heat resistance at high temperatures to the cured product. The heat stabilizer imparts stability at high temperatures to the cured product. Examples of light stabilizers include ultraviolet absorbers that prevent deterioration due to ultraviolet rays, light blocking agents that block light, and quenchers that have a quenching function that receives light energy absorbed by an organic material and stabilizes the organic material. The hydrolysis inhibitor suppresses deterioration due to moisture. The deterioration inhibitor may be at least one selected from the group consisting of antioxidants, heat stabilizers, and ultraviolet absorbers. As the deterioration inhibitor, only one of the components exemplified above may be used, or two or more may be used in combination. In order to obtain a better effect, two or more deterioration inhibitors may be used in combination.
[0057] The curable resin composition may be prepared as a resin varnish in which each of the above-mentioned components is dissolved or dispersed in an organic solvent. The organic solvent is not particularly limited, and examples thereof include aromatic hydrocarbons such as toluene, xylene, mesitylene, cumene, and p-cymene; cyclic ethers such as tetrahydrofuran and 1,4-dioxane; ketones such as acetone, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclohexanone, and 4-hydroxy-4-methyl-2-pentanone; esters such as methyl acetate, ethyl acetate, butyl acetate, methyl lactate, ethyl lactate, and γ-butyrolactone; carbonates such as ethylene carbonate and propylene carbonate; and amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone. From the viewpoint of solubility and boiling point, toluene or N,N-dimethylacetamide may be used. These organic solvents may be used alone or in combination of two or more. The solid content (components other than the organic solvent) concentration in the resin varnish may be 20 to 80% by mass.
[0058] The above-mentioned resin varnish can be mixed and kneaded by using a suitable combination of a conventional mixer, a mixing machine, a three-roll mill, a ball mill, or other dispersing machine.
[0059] [Curable films and laminated films] The curable film according to the present embodiment is made of the above-mentioned curable resin composition. The curable film can be easily produced, for example, by applying a resin varnish containing the curable resin composition to a substrate film and removing the solvent from the coating. According to this method, a laminated film including a substrate film and a curable film provided on the substrate film can be obtained.
[0060] The solvent is removed from the coating film on the substrate film by drying at a temperature at which the curable resin composition does not cure and under conditions where the solvent sufficiently volatilizes. Specifically, the coating film is usually dried by heating at 60 to 180°C for 0.1 to 90 minutes. The preferred residual volatile content of the obtained curable film is 10 mass% or less. When the residual volatile content is 10 mass% or less, it is easy to prevent voids from remaining inside the cured product due to foaming caused by solvent evaporation during assembly and heating. In addition, it is easy to prevent contamination of surrounding materials or members due to volatile components generated during heating.
[0061] The material of the base film is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene; polycarbonate, polyamide, polyimide, polyamideimide, polyetherimide, polyethersulfide, polyethersulfone, polyetherketone, polyphenylene ether, polyphenylene sulfide, polyarylate, polysulfone, and liquid crystal polymers. Among these, from the viewpoint of flexibility and toughness, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polypropylene, polycarbonate, polyamide, polyimide, polyamideimide, polyphenylene ether, polyphenylene sulfide, polyarylate, or polysulfone are preferred.
[0062] The thickness of the base film may be appropriately changed depending on the desired flexibility, but may be 3 to 250 μm. In general, a thickness of 3 μm or more provides sufficient film strength, and a thickness of 250 μm or less provides sufficient flexibility. From the above viewpoints, the thickness of the base film may be 5 to 200 μm, 7 to 150 μm, or 10 to 100 μm. From the viewpoint of improving the peelability from the curable film, a base film that has been subjected to a release treatment with a silicone compound, a fluorine-containing compound, or the like may be used as necessary.
[0063] If necessary, a protective film may be attached onto the curable film to form a laminated film having a three-layer structure consisting of a base film, a curable film, and a protective film.
[0064] The material of the protective film is not particularly limited, and examples thereof include polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefins such as polyethylene and polypropylene. Among these, polyesters such as polyethylene terephthalate; and polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of flexibility and toughness. From the viewpoint of improving the peelability from the curable film, a protective film that has been subjected to a release treatment with a silicone compound, a fluorine-containing compound, or the like may be used as necessary.
[0065] The thickness of the protective film may be appropriately changed depending on the desired flexibility, but may be 10 to 250 μm. In general, a thickness of 10 μm or more provides sufficient film strength, and a thickness of 250 μm or less provides sufficient flexibility. From the above viewpoints, the thickness of the protective film may be 10 to 200 μm, 15 to 150 μm, or 20 to 100 μm.
[0066] The thickness of the curable film after drying is not particularly limited, but may be usually 5 to 1000 μm. When the thickness is 5 μm or more, the curable film or its cured product tends to easily obtain sufficient strength. When the thickness is 1000 μm or less, drying can be performed sufficiently, so that the amount of residual solvent in the curable film tends to be easily reduced.
[0067] The laminate film can be easily stored, for example, by being wound into a roll, or the laminate film can be stored in the form of a sheet cut into a suitable size from the roll.
[0068] The curable resin composition, curable film, and laminate film according to the present embodiment are suitable for forming a protective layer (coverlay) that covers an electric circuit in a printed wiring board, and as an interlayer adhesive in a multilayer printed wiring board, and are particularly suitable as an interlayer adhesive.
[0069] [Printed wiring board] The printed wiring board in this embodiment includes, as a component, a laminate formed of a metal part forming an electric circuit (conductor circuit) and a resin base material. The printed wiring board can be manufactured by a conventionally known method such as a subtractive method using a metal-clad laminate. The printed wiring board in this embodiment is a general term for so-called flexible circuit boards (FPCs), flat cables, circuit boards for tape automated bonding (TAB), etc., in which a conductor circuit formed by a metal part is partially or entirely covered with a coverlay film or screen printing ink, etc., as necessary.
[0070] The printed wiring board of the present embodiment may have any laminated structure that can be used as a printed wiring board. For example, the printed wiring board may have a base layer, an adhesive layer, a metal portion, and a protective layer.
[0071] Furthermore, if necessary, two or more of the above printed wiring boards can be laminated using an interlayer adhesive to form a multilayer printed wiring board.
[0072] In the printed wiring board of this embodiment, as the base material layer, any base material that has conventionally been used as a base material for printed wiring boards can be used.
[0073] In the printed wiring board of this embodiment, any resin that has been conventionally used as a substrate for printed wiring boards can be used as the substrate layer. Examples of the resin for the substrate layer include polyester resin, polyamide resin, polyimide resin, polyamideimide resin, liquid crystal polymer, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resin, and fluorine-based resin (PTFE, etc.) such as polytetrafluoroethylene (PTFE).
[0074] The curable resin composition of this embodiment can be used for each adhesive layer, protective layer, and interlayer adhesive of a printed wiring board. In particular, when these layers are formed using the curable resin composition of this embodiment, they have excellent embedding properties and moldability, and the layer formed using the curable resin composition itself has excellent low dielectric properties and a low linear expansion coefficient. The cured product of the curable resin composition of this embodiment tends to have excellent adhesion to materials constituting a printed wiring board, such as a base layer and a metal part, in particular to low-polarity base materials such as liquid crystal polymers, polyphenylene sulfide, syndiotactic polystyrene, polyolefin resins, and PTFE. Therefore, the curable resin composition of this embodiment is suitable as an interlayer adhesive for a multilayer printed wiring board. The curable resin composition of this embodiment is also suitable as a curable resin composition used for a coverlay film, a laminate, a copper foil with resin, and a bonding sheet. In addition, since the curable resin composition of this embodiment contains a rubber component (A), the cured product can have flexibility. Therefore, the curable resin composition of this embodiment can be suitably used for forming a protective layer and as an interlayer adhesive for a flexible printed wiring board.
[0075] In the printed wiring board of this embodiment, the metal portion is not particularly limited, but may be copper from the viewpoint of wiring formability. The material forming the copper is not particularly limited, and for example, electrolytic copper foil and rolled copper foil used in copper-clad laminates and printed wiring boards can be used. Examples of commercially available electrolytic copper foils include F0-WS-18 (manufactured by Furukawa Electric Co., Ltd., product name), NC-WS-20 (manufactured by Furukawa Electric Co., Ltd., product name), YGP-12 (manufactured by Nippon Denkai Co., Ltd., product name), GTS-18 (manufactured by Furukawa Electric Co., Ltd., product name), F2-WS-12 (manufactured by Furukawa Electric Co., Ltd., product name), and F2-WS-18 (manufactured by Furukawa Electric Co., Ltd., product name). Examples of rolled copper foils include TPC foil (manufactured by JX Metals Co., Ltd., product name), HA foil (manufactured by JX Metals Co., Ltd., product name), HA-V2 foil (manufactured by JX Metals Co., Ltd., product name), and C1100R (manufactured by Mitsui Sumitomo Metal Mining Co., Ltd., product name). From the viewpoint of adhesion to the cured product of the curable resin composition of the present embodiment, a copper foil that has been subjected to a roughening treatment may be used. From the viewpoint of folding resistance, a rolled copper foil may be used. In addition, the metal part may have a roughened surface formed by a roughening treatment. EXAMPLES
[0076] The present disclosure will be described in more detail with reference to the following examples, although the present disclosure is not limited to these examples.
[0077] [Activated ester of alkylphenol resin] (B) As an active ester type curing agent, the following active esterified products of alkylphenol resins were synthesized.
[0078] (Synthesis Example 1) 15.3 g of alkylphenol resin (softening point: about 90°C, manufactured by Resonac Corporation, product name "PR1501"), 19.5 g of isophthalic acid chloride, 13.9 g of α-naphthol, and 113.9 g of toluene were mixed and dissolved, and then 0.11 g of tetrabutylammonium bromide was added to obtain a mixed liquid. 38.5 g of a 20% by mass aqueous solution of sodium hydroxide was dropped into the mixed liquid, and an esterification reaction was carried out while stirring at room temperature for 1 hour. The progress of the esterification was monitored by measuring the infrared absorption spectrum of the reaction product, and the 3500 cm -1 The disappearance of the peak near 1750 cm -1 Peaks around 1200 cm originating from carbon-oxygen bonds (CO) -1 This was confirmed by an increase in the peak around the peak. After the reaction was completed, the reaction solution was left to stand and separated into an aqueous layer and a toluene layer, and the aqueous layer was removed. The toluene layer was washed with water until the pH of the aqueous layer reached 7.0, yielding a toluene solution (solids concentration 30%) of "PR1501-Es," an active ester of alkylphenol resin.
[0079] (Synthesis Example 2) A toluene solution (solid concentration 30%) of "PR1140-Es", an active ester of alkylphenol resin, was obtained in the same manner as in Synthesis Example 1, except that the alkylphenol resin (PR1501) was changed to 19.5 g of alkylphenol resin (softening point: about 130°C, manufactured by Resonac Corporation, product name "PR1140").
[0080] [Curable resin composition] (Examples 1 to 4 and Comparative Examples 1 to 5) The materials shown in Table 1 were mixed in the solid content ratios (unit: parts by mass) shown in the same table to prepare the curable resin compositions of the examples. The materials shown in Table 2 were mixed in the solid content ratios (unit: parts by mass) shown in the same table to prepare the curable resin compositions of the comparative examples. The curable resin compositions were prepared by adding toluene as a solvent so that the solid content was 40 mass%. Details of each material are shown below.
[0081] (A) Rubber component FG1924: Maleic anhydride modified SEBS elastomer (Kraton Polymer Japan Co., Ltd., product name "KRATON FG1924 GT", Mw: 127000, maleic anhydride modification rate: 1.0% by mass)
[0082] (B) Compound having an epoxy group HP7200L: Dicyclopentadiene type epoxy resin (DIC Corporation, product name "EPICLON HP-7200L", epoxy equivalent: 247g / eq, Mn: 288, Mw: 401)
[0083] (C) Active ester type hardener PR1501-Es: Active ester of alkylphenol resin (Synthesis Example 1) PR1140-Es: Active ester of alkylphenol resin (Synthesis Example 2) HPC8150-62T: active ester having a naphthalene skeleton (manufactured by DIC Corporation, product name "EPICLON HPC8150-62T", toluene solution with a solid content of 62% by mass) (C') Phenol-based hardener PR1501: Alkylphenol resin (manufactured by Resonac Corporation, product name "PR1501")
[0084] (D) Curing accelerator 1B2MZ: 1-benzyl-2-methylimidazole (manufactured by Shikoku Chemical Industry Co., Ltd., product name "1B2MZ")
[0085] (E) Filler SC2050-MB: Epoxy group modified silica filler dispersion (manufactured by Admatechs Co., Ltd., product name "SC2050-MB", average particle size: 0.50 μm, solvent: MEK, solid content: 70% by mass)
[0086] [Laminated film] A release-treated polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "Purex A3100", thickness 25 μm) was prepared as a base film. The above-mentioned curable resin composition was applied onto the release-treated surface of this PET film using a knife coater (manufactured by Yasui Seiki Co., Ltd., product name "SNC-350"). The coating film was dried by heating at 80°C for 15 minutes in a dryer (manufactured by Futaba Scientific Co., Ltd., product name "MSO-80TPS") to form a curable film with a thickness of 30 μm. A release-treated PET film identical to the base film was attached as a protective film to the formed curable film with the release-treated surface facing the curable film, to obtain a laminated film. Note that the curable resin composition of Comparative Example 2 was separated, and a laminated film could not be produced.
[0087] (Melt Viscosity) The base film and protective film were removed from the laminated film to leave only the curable film, and the minimum melt viscosity of this curable film was measured using a viscoelasticity measuring device (manufactured by TA Instruments, product name "ARES-G2", heating rate: 3°C / min, temperature range: 30 to 200°C, load: 0.2 N, frequency: 1 Hz, strain: 1%).
[0088] (Flow volume) The curable film, from which the protective film had been removed from the laminated film, was laminated to a polyimide film (UBE Corporation, product name "Upilex-S 50S") using a vacuum pressure laminator (Nikko Materials Co., Ltd., product name "V130") under conditions of a pressure of 0.5 MPa, a temperature of 100°C, and a pressure time of 1 minute to produce a laminate. A hole with a diameter of 10 mm was formed in the laminate using a punching machine, and then the base film was peeled off. Next, a PET film (UBE Corporation, product name "Purex A3100", thickness 25 μm) was placed on the polyimide film side, and an electrolytic copper foil (Furukawa Electric Co., Ltd., product name "F2-WS-18", thickness 18 μm) was placed on the curable film side with the roughened surface facing the curable film side, and a single-sided copper-clad laminate was produced using a small vacuum press (Imoto Manufacturing Co., Ltd., model "IMC-18EE-A type"). The pressing conditions were a pressure of 3 MPa, a temperature increase from 30°C to 180°C at 3°C / min in a vacuum, and a holding time of 60 minutes at 180°C. After the heat pressing, the length of the cured material of the curable film that flowed into the punched holes was measured at eight points, and the average value was taken as the flow amount.
[0089] (Adhesiveness) The protective film of the laminated film was peeled off, and an electrolytic copper foil (manufactured by Furukawa Electric Co., Ltd., product name "F2-WS-18", thickness 18 μm) (hereinafter also referred to as "VLP-Cu foil") having a roughened surface with a surface roughness Rz of 1.8 μm was placed on the exposed curable film. At this time, the VLP-Cu foil was placed on the curable film with the roughened surface facing the curable film. In this state, the VLP-Cu foil was laminated on the curable film using a vacuum pressure laminator (manufactured by Nikko Materials Co., Ltd., product name "V130") under conditions of a pressure of 0.5 MPa, a temperature of 100°C, and a pressure time of 1 minute. Next, the base film was peeled off, and the VLP-Cu foil was placed on the exposed curable film with the roughened surface facing the curable film, and the VLP-Cu foil was laminated on the curable film under the above conditions. Thereafter, the laminate was heated at 180°C for 60 minutes in a dryer (manufactured by Futaba Scientific Co., Ltd., product name "MSO-80TPS") to obtain a laminate having a VLP-Cu foil, a cured film which is the cured product of the curable film, and the VLP-Cu foil.
[0090] A sample for measuring peel strength, 100 mm long and 5 mm wide, was cut out from the obtained laminate. One of the VLP-Cu foil surfaces of this sample was fixed to a glass plate with an epoxy adhesive (Huntsman Japan, product name "Araldite Rapid"). Using an autograph (Shimadzu Corporation, product name "EZ-LX"), the other VLP-Cu foil and the cured film were gripped with a jig at a pulling speed of 50 mm / min, and a 90-degree peel test was performed to peel them off from the VLP-Cu foil fixed to the glass plate.
[0091] (Dielectric properties) The laminated films obtained in the examples and comparative examples were heated at 180°C for 60 minutes to cure the curable films, forming cured films. The base film and protective film were removed from the cured film, and the cured film was cut to a size of 60mm x 60mm to obtain test pieces. Using these test pieces, the relative dielectric constant (Dk) and dielectric loss tangent (Df) were calculated by the SPDR (Split Post Dielectric Resonators) method. The measurement was performed using a vector network analyzer E8364B (manufactured by Keysight Technologies), CP531 (manufactured by Kanto Electronics Application Development Co., Ltd.), and CPMA-V2 (program), respectively, at an ambient temperature of 25°C and a frequency of 10GHz.
[0092] [Table 1]
[0093] [Table 2]
Claims
1. (A) a rubber component, (B) a compound having an epoxy group, (C) an active ester type curing agent, (D) a curing accelerator, and (E) a filler, The curable resin composition, wherein the (C) active ester type curing agent contains an active ester of an alkylphenol resin.
2. The curable resin composition according to claim 1, which is used as an interlayer adhesive for a multilayer printed wiring board.
3. 2. The curable resin composition according to claim 1, wherein a content of the active ester type curing agent (C) is 1 to 40 parts by mass with respect to 100 parts by mass of a total amount of the rubber component (A), the compound having an epoxy group (B), and the active ester type curing agent (C).
4. The curable resin composition according to claim 1, wherein the compound (B) having an epoxy group has a weight average molecular weight of 200 to 1,000.
5. 2. The curable resin composition according to claim 1, wherein a content of the curing accelerator (D) is 0.1 to 10 parts by mass per 100 parts by mass of a total amount of the rubber component (A), the compound having an epoxy group (B), and the active ester type curing agent (C).
6. The curable resin composition according to claim 1 , wherein the (E) filler comprises a surface-treated filler.
7. The curable resin composition according to claim 6 , wherein the surface-treated filler comprises a filler having at least one group selected from the group consisting of an epoxy group, a vinyl group, and a phenylamino group.
8. A curable film comprising the curable resin composition according to any one of claims 1 to 7.
9. A laminate film comprising: a base film; and the curable film according to claim 8 provided on the base film.
10. An active ester type curing agent, which contains an active ester of an alkylphenol resin.
Citation Information
Patent Citations
Laminate with adhesive layer, and flexible copper-clad laminate plate and flexible flat cable using the same
JP2018150543A